Efektivitas Media Pembelajaran berbasis Augmented Reality pada Mata Pelajaran Informatika terhadap Hasil Belajar Siswa di SMA Negeri 1 Paguat - Rahmat Darmawan Paputungan; Dian Novian; Bait Syaiful Rijal (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to determine the effectiveness of Augmented Reality (AR)-based learning media on students' learning outcomes in the Informatics subject at SMA Negeri 1 Paguat. The study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The research sample consisted of 60 students divided into an experimental group and a control group. Data were collected through learning achievement tests, classroom observations, and interviews. The research instrument consisted of multiple-choice questions that had been tested for validity and reliability. Data were analyzed using IBM SPSS through normality testing, homogeneity testing, N-Gain analysis, Paired Samples t-Test, and Independent Samples t-Test. The results revealed that the use of AR-based learning media had a significant positive effect on improving students' learning outcomes. The experimental group demonstrated greater improvement in learning outcomes than the control group after receiving instruction using AR-based media. Furthermore, the implementation of AR enhanced students' engagement and learning motivation through interactive visualizations and three-dimensional simulations of computer networking concepts. Therefore, Augmented Reality-based learning media can be considered an effective instructional tool for improving students' learning outcomes in Informatics education.